Measurements of inelastic electron scattering from molecular oxygen at high scattering angles - Linert, Ireneusz; Mielewska, Brygida; Zubek, Mariusz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
Inelastic electron scattering from molecular oxygen has been studied for high scattering angles, from 90° to 180°, at the electron incident energy of 10 eV using magnetic angle-changing technique. Excitation of vibrational levels v = 1–9 of the X3Sg– ground state and v = 0 of the a1Dg first excited state of oxygen has been observed. From the measured energy loss spectra differential cross-section for excitation of v = 1 vibrational level of the X3Sg– state has been determined in the above scattering angle range. In the measurements a newly constructed double hemispherical electrostatic electron spectrometer has been employed which incorporates a recently designed conical magnetic angle-changer.
Optica Applicata, Vol. 36, 2006, nr 4, s. 551-557
Keywords: optyka; electron collisions; oxygen; differential cross-sections; magnetic angle changer